Training for performance: Insights from molecular biology - Coffey, V. G.; Hawley, J. A. (International Journal of Sports Physiology and Performance, 2006)
World records for performances over a wide range of athletic events continue to improve on a regular basis. In the search for novel and better methods of preparation for competition, scientists, coaches, and practitioners constantly seek out the latest information on training, nutrition, and other related disciplines in an attempt to gain a competitive edge for athletes. With recent advances in technology such as real-time polymerase chain reaction (RT-PCR), high-throughput chip analyses, and new and improved antibodies, several techniques are now readily available to study the effects of various training interventions on a variety of early-response genes and signaling proteins in skeletal muscle. Although it cannot presently be claimed that such scientific endeavors have influenced the training practices of elite athletes, these new and exciting technologies have provided insight into how current training techniques result in specific muscular adaptations and might ultimately provide clues for future and novel training methodologies. In this commentary we discuss the molecular basis of the training adaptation and review the role for several key signaling proteins important in the adaptation to endurance and resistance training.